Exploration of an ultrasonic pulse echo system for comparison of milks, creams, and their dilutions. (January 2021) - Yang, Yuzheng; Wright, William M.D.; Hettinga, Kasper A.; van Ruth, Saskia M.
Abstract: Rapid measurements are valuable in food authentication. As a first step towards application of sound for fast food authentication, the influence of fat content and dilution of liquid milk/cream products on their ultrasound characteristics was examined. A total of 18 liquid dairy products, ranging in fat content from 0 to 60 g/100 g product, including nine cream samples and nine milk samples, were diluted to four levels, which resulted in 90 samples. Ultrasonic velocity, together with physical properties including viscosity, density, and macronutrient composition of the tested dairy products, was determined. The results show that the ultrasonic velocity in the dairy products increased with a decreasing fat content of the samples. There was a significant positive correlation between the velocity and density, which was further related to the impact of the fat content. Water dilution caused different changes in velocity, depending on the ratio of fat content and continuous phase of the samples. A higher fat content of the samples resulted in a smaller effect of dilution on velocity. This study showed that the ultrasonic system allows rapid and non-destructive analysis for comparison of liquid dairy samples and appears promising for detection of dilution. Highlights: Ultrasonic velocity in dairy products of various fat contents is determined. Ultrasonic velocity in undiluted dairy products is impacted by the fat content. Velocity changes caused by dilution depend on the ratio of fat and plasma contents. Higher fat content results in a smaller velocity change caused by dilution.